Pemberdayaan Ekonomi Masyarakat Melalui Koperasi dalam Perspektif Maqashid Syariah - Nuril Lailia, Risma; Mukhsinin Syua’ibi, Moh.; Dayat, M. (Kartika: Jurnal Studi Keislaman, 2025)
This research is motivated by the effectiveness of cooperatives in improving the welfare of member farmers, especially through the Maqashid Syariah approach. The purpose of this study is to analyze the role of the Setia Kawan Dairy Farmers Cooperative (KPSP) in economic empowerment, the challenges faced and how the solutions provided by KPSP, and the extent to which KPSP Setia Kawan adopts the principles of Maqashid Syariah in all its operational activities. The method used is qualitative descriptive through observation, interview, and documentation techniques. The results of this study indicate that KPSP Setia Kawan has an important role in improving the economic welfare of its members as evidenced by the achievements of its members, and in its operational activities KPSP has applied the principles of Maqashid Syariah such as hifz al-mal, hifz al-nafs, hifz al-nasl, hifz al-din, and hifz al-aql. The implication is that cooperatives need to strengthen the spiritual aspects and economic sustainability in order to create broader benefits.